The process of formation studying motivation as a way to successful professional training of interns-pediatricians - Kolyubakina, L. V.; Khilchevska, V. S. (Journal of Education, Health and Sport, 2017)
The paper analyzes results of anonymous questionnaire of interns in pediatrics to assess motivation during the internship.